Mobilities in the crisis and post-crisis times: migration strategies of Poles on the EU labour market. Issue 10 (8th August 2016) - Janicka, Anna; Kaczmarczyk, Paweł
ABSTRACT: In the post-enlargement period, hundreds of thousands of 'new Europeans' from the New Member States embarked on their migration journeys in search of better jobs and living conditions. With over two million citizens staying temporarily abroad, Poland became one of the most important migrant sending countries in Europe. A few years after the 2004 enlargement round, most of the EU-15 labour markets and immigrants themselves were confronted with the most severe economic crisis since the 1930s. Such circumstances are presented as a test of how migration flows respond to changes in economic conditions and to what extent they may increase the adjustment capabilities of labour markets. Against this background, this article takes the migration of Poles as a case study in exploring the ways in which migrants respond to crisis-driven changes in the socio-economic environment. Based on two complementary data sets, we analyse the structural features of Polish migration and the strategies of mobile Poles on the EU labour market. The results indicate that links between the crisis and migration are more nuanced than suggested by economic theory. Furthermore, we show that labour market impulses can be effectively realigned by other factors of both economic and social nature such as access to welfare benefits or family-related strategies.